Development of LKPD Based on Contextual Teaching and Learning in Social Studies Lessons to Improve the Higher Level Thinking Skills of Grade IV Students of SDN Inpres Buncu - Zihan Maulani Masrun (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
This research aims to develop Contextual Teaching and Learning (CTL)-based Student Worksheets (LKPD) in science subjects to improve the SDN Inpres Buncu's grade IV pupils' Higher Order Thinking Skills (HOTS). The ADDIE model, which comprises the phases of analysis, design, development, implementation, and evaluation, is used in this development research. The study participants included expert validators (materials, media) and class IV students. Questionnaires for expert validation, instructor response, and student response are examples of data gathering tools. lifts, learning implementation observation sheets and test sheets. The validation results showed that LKPD was very feasible with a percentage of material experts of 91% and media experts of 92% indicating that LKPD was under the "very feasible" category. The teacher's response questionnaire serves as the practicality test obtained a score of 95% and the student response questionnaire obtained a score of 93%, both in the "Very Practical" category. In addition, the results of observation of learning implementation also show a high level of practicality with a percentage of 95%. The effectiveness test through the pre-test and post-test showed an increase in score with an N-Gain of 0.71 (high-effective category) which signified a significant improvement in high-level thinking ability. Thus, this CTL-based LKPD is declared valid, practical, and effective to be used in social studies learning to support the improvement of students' KBTT.